Complex Management of Takayasu Arteritis with Multiorgan Involvement: A 4-Year Follow-up Case Report - Raphy, Glen Loui; Parveen, CS Riya; John, Thomas; Marri, Anushka Reddy; Sangam, Shreya (Indian Journal of Pharmacy Practice)
Takayasu Arteritis (TA) is a rare vasculitis characterised by inflammation primarily affecting the aorta and its branches, predominantly observed in young Asian females. This case report documents the clinical journey of a 28-year-old Asian male diagnosed with TA over a four-year period. Initially presenting with claudication and chest pain, the patient was found to have extensive coronary, pulmonary and renal artery involvement. Recurrent hospitalisations ensued due to complications including anaemia, accelerated hypertension, renal failure and sepsis. Management challenges arose, complicated by adverse drug reactions and the necessity for haemodialysis. Effective management of TA mandates early diagnosis, judicious employment of immunosuppressive therapy and vigilant monitoring. This case underscores the essential role of a multidisciplinary approach and personalised care in navigating the complex challenges posed by TA. It emphasises the importance of clinician awareness of diagnostic criteria, facilitating timely intervention and optimising patient outcomes. By elucidating the intricate nuances of TA management, this report contributes to a deeper understanding of this rare disease and advocates for tailored therapeutic strategies addressing the complexities of individual patient presentations.
Keywords: Takayasu arteritis; Renal failure; Pulmonary arterial hypertension; Coronary artery disease; Myocardial infarction; Cardiomyopathy; Acute coronary syndrome; Congestive heart failure; Dialysis